Structural–functional diversity of CD47 proteoforms - Zhang, Ting; Wang, Feng; Xu, Lu; Yang, Yong-Guang (Frontiers in Immunology, 2024)
The ubiquitously expressed transmembrane glycoprotein CD47 participates in various important physiological cell functions, including phagocytosis, apoptosis, proliferation, adhesion, and migration, through interactions with its ligands, including the inhibitory receptor signal regulatory protein α (SIRPα), secreted glycoprotein thrombospondin-1 (TSP-1), and integrins. Elevated expression of CD47 is observed in a wide range of cancer cells as a mechanism for evading the immune system, blocking the interaction between the CD47 and SIRPα is the most advanced and promising therapeutic approach currently investigated in multiple clinical trials. The widely held view that a single type of CD47 protein acts through membrane interactions has been challenged by the discovery of a large cohort of CD47 proteins with cell-, tissue-, and temporal-specific expression and functional profiles. These profiles have been derived from a single gene through alternative splicing and post-translational modifications, such as glycosylation, pyroglutamate modification, glycosaminoglycan modification, and proteolytic cleavage and, to some extent, via specific CD47 clustering in aging and tumor cells and the regulation of its subcellular localization by a pre-translational modification, alternative cleavage and polyadenylation (APA). This review explores the origins and molecular properties of CD47 proteoforms and their roles under physiological and pathological conditions, mentioning the new methods to improve the response to the therapeutic inhibition of CD47-SIRPα immune checkpoints, contributing to the understanding of CD47 proteoform diversity and identification of novel clinical targets and immune-related therapeutic candidates.We have previously identified the corresponding isoform in murine testis tissue (unpublished).